Factors Determining the Brand Preference of Tv-with Special Reference to Thoothukudi District in Tamil Nadu - Ravichandran, K.; Narayanarajan, S. (Indian Journal of Marketing, 2004)
The topic of brand preference has drawn substantial attention in recent years, as a field of study and it is fair to say that much has been learned. It is a dynamic field and many discoveries are still to be made. The study of brand preference poses important problems for both marketers and consumers. The brand preference of consumer durables is largely influenced by a number of factors such as advertisement, price, quality, performance, after-sales service and the like. These factors play a vital role in the decision-making process and in the brand preference. In this article, an attempt is made to analyze the factors determining the brand preference of TV.